Simulação de iluminação natural em prédios para planejamento sustentável de cidades - Diesel, Ivan Rogério (Universidade do Vale do Rio dos Sinos, 2014)
Contemporaneously, cities are becoming more vertical, it is difficult to design urban spaces in which light and heat from the sun would attain the ground and lower floors of urban buildings in a way that does not harm the health of the population. Given the physical limitations to the analysis of the degree of natural lighting of a large number of buildings, it is necessary to simulate it by computer modeling. Parameters such as geographical location, height, number and distance between buildings are used to identify levels of solar radiation and the resulting environmental and technological challenges to be overcome for the sustainability. The objective of this work is to analyze the degree of outside natural lighting in urban areas to seek a technical solution in order to provide the suitable human conditions of lighting and temperature. For this, a model lighting of buildings that includes simulations that allow both the analysis of the degree of illumination building as the analysis of the degree of global illumination on a large set of buildings is presented. The result is presented using the technique of PCA.
Keywords: Computação gráfica; Simulação de nível de iluminação; Programação; Computer graphics; Simulation illumination level; Programming technical; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação